Discovery of a Mesoproterozoic granite in the northern Alxa Block and its tectonic implication. Issue 9 (30th May 2022) - Yu, Wei; Shao, Zhaogang; Niu, Manlan; Su, He
Abstract : A Mesoproterozoic granite covering about 5 km 2 is firstly recognized in the Zhusileng area, which is located between the northern Alxa Block and the South Gobi microcontinent. New geochronological data from this area provide new insight for understanding the Precambrian crustal evolution of the middle segment of the southern Central Asian Orogenic Belt (CAOB). Based on the crystal shapes, internal textures, and high Th/U ratios, the zircons from this Mesoproterozoic granite are interpreted as magmatic origin. Meanwhile, LA‐ICP‐MS zircon U–Pb dating shows that it was emplaced at 1458 ± 7.5 Ma. Published geochronological data and Sr–Nd isotopic compositions of igneous rocks from the Zhusileng area and its vicinity are also compiled in this study. The Late Palaeozoic granitoids from the Zhusileng area have strongly negative εNd (t) values (−0.1 to −10.8), high ( 87 Sr/ 86 Sr)i (0.69657–0.73423) and old Nd model ages (0.9–1.8 Ga), suggesting the existence of Precambrian microcontinent in the Zhusileng area. Furthermore, the statistical analysis (or isotopic mapping) of Sr–Nd isotopic compositions of Palaeozoic granitoids from the middle segment of the southern CAOB also displays similar εNd (t) values and relatively old Nd model ages along the Hanshan Block, Zhusileng, Tsaggan Uul terrane, and Hutag Uul terrane. Therefore, we propose that those units may share a common basement during Mesoproterozoic to Early Neoproterozoic. Abstract : Integrating the new zircon U–Pb ages of gneissic granites, published geochronological data and Nd isotopic compositions of igneous rocks from the northern Alxa Block and its vicinity, we propose that the ZHTZ, Hanshan Block, Tsaggan Uul terrane, and the Hutag Uul terrane may share a common Precambrian crystalline basement, which may constitute the Late Riphean South Gobi microcontinent.